Mechanical design and analysis of a pneumatic ankle foot orthosis - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
The purpose of this paper is to present the mechanical design and analysis of pneumatic ankle foot orthosis (PAFO) device which can be used for assisting and rehabilitation of ankle foot that has impairments. Some of these impairments are cerebral palsy, multiple sclerosis and muscular dystrophies. The PAFO assists the ankle during dorsiflexion and plantar flexion by way of pneumatic artificial muscle and pneumatic rotary actuator. The designed PAFO is also equipped with various sensors such as force, position and accelerometer. The lightweight and portable design that based on biomechanical studies is built with carbon fiber material. The mechanical design is done in SolidWorks. The PAFO that design has been analyzed using Matlab/SimMechanics to determine the ankle joint torque requirement during gait. The results of the analysis have showed the biomechanical suitability of PAFO device. © 2018 IEEE.
Keywords: Ankle foot orthosis; assistive device; biomechanics; PAFO; pneumatic; simmechanics